Understanding immunotherapy terminology: An analysis of provider‐patient conversations - Blee, Shannon; Rosenberg, Bari; Switchenko, Jeffrey M.; Hianik, Rachel; Thomson, Mary Catherine; Dixon, Margie; Bilen, Mehmet Asim; Pentz, Rebecca D. (Immunomedicine, 2021)
Background Immunotherapy terminology is complex and can be difficult for patients to understand, threatening informed consent. The aims of this exploratory study are to determine whether patients understand immunotherapy terminology and if the provider defining the term improves patient understanding. Good patient/provider communication is important for good informed consent, patient adherence to treatment and patient outcomes. Methods Conversations between oncology providers and patients discussing immunotherapy were observed (n = 39), and technical terms used were noted. With consent, patients were interviewed post‐conversation to assess their understanding of these terms (n = 39). Comparisons of the terms were conducted using chi‐square tests, Fisher's exact tests, or ANOVA where appropriate. Results “Immunotherapy” was the most difficult for participants to understand with 48.7% (19/39) correctly defining immunotherapy. “Immunotherapy agents” was understood 53.8% (14/26) of the time. “Immune system” was well understood 88.5% (23/26). Providers defined immunotherapy in 97.4% of conversations. There was no correlation between having immunotherapy defined in the conversation, and the likelihood of a correct definition (p = 0.487). “Immune system” was defined in 92.3% of conversations (n = 26), and defining it in the conversation was correlated with increased patient understanding (p = 0.009). Conclusion Our results indicate that patients have difficulty understanding some immunotherapy terminology. Since patient understanding of key terminology is crucial for informed consent and patient care, it is essential to implement interventions to improve understanding.